2006
DOI: 10.1093/bioinformatics/btl079
|View full text |Cite
|
Sign up to set email alerts
|

Predicting protein interaction sites: binding hot-spots in protein–protein and protein–ligand interfaces

Abstract: The resulting differences between predicting binding-sites at protein-protein and protein-ligand interfaces are striking. There is a high level of prediction accuracy (< or =93%) for protein-ligand interactions, based on the following attributes: van der Waals potential, electrostatic potential, desolvation and surface conservation. Generally, the prediction accuracy for protein-protein interactions is lower, with the exception of enzymes. Our results show that the ease of cleft desolvation is strongly predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 54 publications
3
120
0
Order By: Relevance
“…2). Surprisingly, KNO 3 and KCl dissociated the complex but KF did not, at least not to the same degree, and K 2 HPO 4 even increased the signal slightly. We then performed pre-equilibrium binding experiments with three different anions: chloride, fluoride, and phosphate.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…2). Surprisingly, KNO 3 and KCl dissociated the complex but KF did not, at least not to the same degree, and K 2 HPO 4 even increased the signal slightly. We then performed pre-equilibrium binding experiments with three different anions: chloride, fluoride, and phosphate.…”
Section: Resultsmentioning
confidence: 88%
“…3 The three-dimensional structure of this protein with and without its target ligand has been solved (11). The canonical PDZ domain consists of about 90 -100 amino acids forming six ␤ strands (␤A to ␤F) and two ␣ helices; ␣A and ␣B neatly arranged in a spherical structure (Fig.…”
mentioning
confidence: 99%
“…It is well known that cation-interactions on the surface of proteins have a stabilizing effect on structure; however, we conclude based on our NMR data that mutations in Trp 30 and Lys 32 do not experience any significant structural destabilization. It is also well established that desolvation penalties can destabilize electrostatic interactions at protein-protein interaction interfaces (43,44) and that the desolvation penalty of a cation-interaction is significantly less than that of a normal electrostatic interaction (45). Given the importance of Lys 32 as an anchoring interaction for huwentoxin-IV binding and activity, it is tempting to speculate that the role of the cation-interaction is to mitigate the energetic cost that would otherwise be associated with desolvation of Lys 32 and thus strengthen the overall equilibrium constant more in favor of binding (anchored by Lys 32 -Glu 811 according to our model).…”
Section: Discussionmentioning
confidence: 99%
“…Nooren et al [23] studied the composition of interacting residues and revealed existing different tendency between those residues from different type of protein complexes. It is suggested that amino acid physicochemical properties may also promote the prediction of binding residues [24-27]. Furthermore, many structural characteristics related to identification of critical residues have been intensively investigated, such as the secondary structure information etc.…”
Section: Introductionmentioning
confidence: 99%